Pandangan akan Masa Depan dan Kematangan Karier Siswa SMK - Nimaswari Dyah Ayu Putri; Arista Adi Nugroho; Pratista Arya Satwika (UNS Press, 2022)
In Indonesia, the unemployment rate by education level is dominated by Vocational High School graduates. One of the factors that can support individual success in determining a career is career maturity. Individuals with good career maturity tend to have better career achievements than individuals with low career maturity. This research aims to determine the correlation between future time perspective and career maturity among vocational high school students of SMK. This research uses stratified cluster random sampling which consist of 312 students from ten majors of grade X, XI, and XII. Further analysis using cluster stratified random sampling. The instruments used were Future Time Perspective Scale (α=0,888) and Career Maturity Scale (α=0,871). The data analysis technique used in this research is Spearman Rho correlation analysis. The result indicates a correlation coefficient of 0, 519, which means that there is a significant positive relationship between outlook on the future and career maturity. The higher the view of the future, the higher the career maturity. Conversely, the lower the view of the future, the lower the career maturity